Telewizyjna kampania referendalna jako arena rywalizacji politycznej. Referendum unijne w Polsce w 2003 r. - Stępińska, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2005)
Polish legal acts stipulate that the purpose of a referendum campaign is to present the attitude of citizens, political parties, associations, foundations and other entities to the subject of the referendum. Thus the content of the messages should refer to the European issues and in particular to the benefits and problems generated by Poland’s accession to the European Union, as well as to the arguments for or against the very accession and the changes Poland and her citizens would face following the result of the vote. However, the analysis of referendum messages broadcast by the state radio and television demonstrates that a significant number of entities that participated in the campaign, in particular of political parties, have used their time in order to present themselves (shaping or modifying their image) or to criticize and fight their political adversaries (by means of a negative campaign, tarnishing the image of opponents and emphasizing the differences between different actors on the political stage). Various instruments of persuasion and political competition were applied to achieve this goal, mainly linguistic tools and the manipulation of sound and picture.